Cutaneous leishmaniasis: an evolving disease with ancient roots. (10th April 2019) - Saliba, Maelle; Shalhoub, Awss; Taraif, Suad; Loya, Asif; Houreih, Mohammad A.; El Hajj, Rana; Khalifeh, Ibrahim
Abstract: Background: Cutaneous leishmaniasis (CL) remains a prioritized neglected tropical disease. CL novel presentations call for updating its features. Methods: A multiregional cohort of 396 patients with confirmed CL was reviewed. Lesion's clinical stage and eruption type were assigned. Disease was considered as extensive if numerous (≥5), large (>3 cm), disfiguring, threatening vital sensory organs, and/or older than 12 months. Microscopically, Ackerman's inflammatory pattern, Ridley's pattern (RP), and parasitic index (PI) were recorded. Microscopic variables pertaining to the organisms, epidermis, and host's inflammatory response were also assessed. All cases were confirmed and speciated molecularly. Results: In our region, 71.8% of cases showed extensive disease with 15.7% exceeding 12 months duration. Leishmania tropica accounted for 91.3% of cases while Leishmania major constituted 8.7% and presented solely as dry lesions. The dominant inflammatory composite consisted of plasma cells, lymphocytes, and histiocytes. Granulomatous inflammation was present in 55.5%. Most cases showed interface changes (72.7%), spongiosis (75.3%), and marked epidermal hyperplasia (63.9%). Transepidermal elimination of organisms was present in 29.2% of cases. None of traditional classification patterns (clinical stage, microscopic pattern, and RP) showed the predicted linear correlation with lesion age. High and low PI levels correlated with early and healing microscopic patterns, respectively, but did not correlate with the corresponding RPs. PI was bimodal with peaks at 3–6 and 9–12 months. Conclusion: Cutaneous leishmaniasis is an evolving disease defying the traditional prediction classifications. Our study sets the ground for adopting updated clinical courses, microscopic presentation, and species mapping.